Time and Tradition as Reflected in the Etz Hayim Torah Commentary. (11th October 2018) - Meirovich, Harvey
Abstract: At the beginning of the twenty‐first century, the Conservative Movement in North America published a Torah commentary reflecting its historical and theological elucidation of Judaism. This commentary, Etz Hayim, evinces a number of features that the following essay subjects to critical comment and analysis. These include: the commentary's emphasis on historical context as critical to deciphering the Torah narratives and its laws; the presupposition that Judaism functions as an organism constantly in flux, open to patterns of progress and decline, with an aptitude for rebirth and self‐renewal; and that the pivotal rubrics of belonging, believing, and behaving are quintessential features of Jewish identity. While these characteristics are relatively uncontroversial, the same cannot be said for the editorial decision to divide, on the same page, the commentary's 'historical' and 'homiletical' segments – a feature which effectively drives underground the option to integrate spiritual values and lessons using the tools of modern critical scholarship. Another unfortunate feature of Etz Hayim is that its two essays on Jewish law (Halakha) offer contrasting, competitive interpretations of how the halakhic process actually works in the minds of Conservative decisors. Yet these alternate approaches are not sufficiently delineated for the lay reader. Finally, while Etz Hayim does highlight value concepts that function as goads to ritual observance, the various contributors to the commentary and to the appended essays never fully engage why Conservative Jews ought to become serious practitioners of Jewish tradition. These shortcomings notwithstanding, Etz Hayim does offer a template of hope and expectation: through its historical‐religious experiences, the Jewish people facilitates an ethical worldview of particular, and of universal, merit.